(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
At present, there is no specific treatment aimed at cure of human lung cancer, a kind of most lethal cancers. Modern allopathy provides only temporary relief of symptoms or severity when used in the form of medicines, radiotherapy or chemotherapy at the cost of moderate to severe side-effects while long term survival or complete cures are anecdotal. It is also well known that surgical interventions, chemo and radiotherapies have failed consistently to cure many varieties of cancers. This hopeless situation demands for newer kind of therapeutic interventions which may not be the conventional modes of therapy. Alternative/complementary medicine from plant sources becomes well worth trying for these cancers as these medicines are quite safe and their effectiveness is worth investigating. We hereby present a case of lung cancer of subtype adenocarcinoma where the patient was certain to die even if the patient could afford conventional allopathic treatment.